2019
DOI: 10.1080/13596748.2019.1584447
|View full text |Cite
|
Sign up to set email alerts
|

Independent learning as class preparation to foster student-centred learning in first-year engineering students

Abstract: , where he teaches Physics and related subjects since 1990. His main area of interest is efficiency and innovation in physics education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…According to Barrineau et al (2009), motivated learners create challenges to learn from each other, hence planning, implementing and evaluating their learning achievements together. Macgowan and Wong (2017) and Zirkus and Morgan (2020) emphasise that collaborative learning is as valuable as individual progress; it increases self-confidence (Chen, 2020) and enhances personal potential (Pejuan & Antonijuan, 2019), and the teacher becomes a role model of appropriate respectful behaviour in the process (Apaydin & Seçkin, 2013). It is important to note that challenges enable a deeper understanding of the analysed phenomena and enhance the pupils' relation with the environment (Davis & Sumara, 2002;Kaukko & Wilkinson, 2020), whereas the purposeful choice of learning and behaviour can strengthen motivation (Anderson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to Barrineau et al (2009), motivated learners create challenges to learn from each other, hence planning, implementing and evaluating their learning achievements together. Macgowan and Wong (2017) and Zirkus and Morgan (2020) emphasise that collaborative learning is as valuable as individual progress; it increases self-confidence (Chen, 2020) and enhances personal potential (Pejuan & Antonijuan, 2019), and the teacher becomes a role model of appropriate respectful behaviour in the process (Apaydin & Seçkin, 2013). It is important to note that challenges enable a deeper understanding of the analysed phenomena and enhance the pupils' relation with the environment (Davis & Sumara, 2002;Kaukko & Wilkinson, 2020), whereas the purposeful choice of learning and behaviour can strengthen motivation (Anderson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Remedial actions are also considered another way of fostering independent learning. Pejuan & Antonijuan (2019) gave remedial actions in the forms of active-learning components for undergraduate students said to have underdeveloped independent learning abilities. Those studies revealed that independent learning for university students is important and needs to be developed for further implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have also been conducted to support this independence process for university students. For example, Pejuan and Antonijuan (2019) implemented remedial actions to foster students' independent learning skills. These actions were applied to first-year engineering students, with positive perceptions obtained towards learning independence.…”
Section: Introductionmentioning
confidence: 99%